Clinical applications of virtual navigation bronchial intervention - Kajiwara, Naohiro; Maehara, Sachio; Maeda, Junichi; Hagiwara, Masaru; Okano, Tetsuya; Kakihana, Masatoshi; Ohira, Tatsuo; Kawate, Norihiko; Ikeda, Norihiko (Journal of Thoracic Disease, 2017)
Background: In patients with bronchial tumors, we frequently consider endoscopic treatment as the first treatment of choice. All computed tomography (CT) must satisfy several conditions necessary to analyze images by Synapse Vincent. To select safer and more precise approaches for patients with bronchial tumors, we determined the indications and efficacy of virtual navigation intervention for the treatment of bronchial tumors. Methods: We examined the efficacy of virtual navigation bronchial intervention for the treatment of bronchial tumors located at a variety of sites in the tracheobronchial tree using a high-speed 3-dimensional (3D) image analysis system, Synapse Vincent. Constructed images can be utilized to decide on the simulation and interventional strategy as well as for navigation during interventional manipulation in two cases. Results: Synapse Vincent was used to determine the optimal planning of virtual navigation bronchial intervention. Moreover, this system can detect tumor location and alsodepict surrounding tissues, quickly, accurately, and safely. The feasibility and safety of Synapse Vincent in performing useful preoperative simulation and navigation of surgical procedures can lead to safer, more precise, and less invasion for the patient, and makes it easy to construct an image, depending on the purpose, in 5–10 minutes using Synapse Vincent. Moreover, if the lesion is in the parenchyma or sub-bronchial lumen, it helps to perform simulation with virtual skeletal subtraction to estimate potential lesion movement. By using virtual navigation system for simulation, bronchial intervention was performed with no complications safely and precisely. Conclusions: Preoperative simulation using virtual navigation bronchial intervention reduces the surgeon’s stress levels, particularly when highly skilled techniques are needed to operate on lesions. This task, including both preoperative simulation and intraoperative navigation, leads to greater safety and precision. These technological instruments are helpful for bronchial intervention procedures, and are also excellent devices for educational training.